Chengdu High School Soft Volleyball Promotion Study: A Case Study of H High School - Li, Siyu (International Journal of Social Sciences and Public Administration, 2024)
Soft volleyball possesses rich technical and fitness values, is practical and economically safe, and is beneficial for the construction of campus sports culture. However, due to various constraints, its promotion within high school campuses is limited in scope and depth. This study analyzes the situation of soft volleyball promotion in a high school in Chengdu through questionnaires and observation methods. The survey results show that most students are willing to participate in soft volleyball, considering it both safe and conducive to social interaction and stress relief; however, some students have had little exposure to soft volleyball and even regard it as a waste of time. Although there are advantages to promoting soft volleyball, there are also certain limitations, requiring improvements in promotional methods. Despite the favorable conditions for promotion, there are also challenges. The conclusions suggest: 1. Incorporating soft volleyball into physical education classes to increase classroom diversity. 2. Increasing the amount of soft volleyball training during sunshine sports exercises. 3. Adding more professional coaches for soft volleyball. 4. Organizing soft volleyball competitions to promote a sports culture of "unity, friendship, and courage to challenge."